A 10-year retrospective analysis (2012-2021) of hospitalizations resulting from dog bites in Southern Italy - Alberghina, Daniela; Virga, Antonino; Sottile, Gianluca; Buffa, Sergio Pio; Panzera, Michele (Frontiers in Veterinary Science, 2023)
This study aimed to describe the incidence and characteristics of dog-bite injury hospitalizations (DBIH) in the largest administrative region of Italy (Sicily) over the ten-year period: 2012-2021. Four hundred and forty-nine cases were analyzed. Patients were divided into seven age groups: preschoolers (0-5 years), school-age children (6-12 years), teenagers (13-19 years), young adults (20-39 years), middle-aged adults (40-59 years), old adults (60-74 years) and the elderly ( 75 years). Association among categorical variables (age, gender, principal injury location) was evaluated using chi-square tests, and mean differences for normally distributed variables were assessed using one-way analysis of variance. Finally, a Poisson regression general linear model (GLM) analysis was used to model incidence data. The results revealed that the incidence of DBIH per 100,000 population increased from 0.648 in 2012 (95%CI 0.565-0.731) to 1.162 in 2021 (95%CI 1.078-1.247, P<0.01). Incidence for both male and female victims also increased over the studied period (P <0.05). We found an increasing trend of incidence in adults between 20 and 59 years of age (P<0.05). Moreover, the most frequently injured age group by dogs was the preschooler group and, whilst we found a lower risk of being injured for males older than 20 years, no difference with females was observed. The location of lesions depended on the age group (P < 0.001). The number of days of DBIH increased significantly with age (P<0.01). The increase of DBIH represents a public health problem that requires the development of preventive approaches.